Evidence of distant hybridization within Central Asian feather grasses (Poaceae: Stipa) - Gudkova, Polina D. (Turczaninowia)
The genus Stipa is one of the largest genera of Poaceae. The phylogeny of the genus is still poorly resolved, and one of the main problems is linked to the extensive inter and intrasectional hybridization. Disclosure of hybridization processes is a key to understanding relationships between species within the genus. During a floristic study in feathergrass steppe ecosystems of central Asia, we found challenging specimens of Stipa with an interesting combination of morphological characters suggesting their origination through hybridization between morphologically and phylogenetically distant species. To confirm our hypothesis, we applied a combination of classical morphological and genome-wide SNP genotyping methods. Using such an approach, we determined that the new taxon named Stipa x smelanskyi arose from crossing S. richteriana and S. drobovii and confirmed that it is an F1 hybrid. Moreover, we found a S. drobovii specimen with a minor admixture of S. richteriana loci that may indicate putative introgression events among these taxa.